(untitled) (Eurasian Medical Research Periodical, 2022)
The results of treatment of 250 patients with inguinal hernias, operated according to the Liechtenstein method, were analyzed. The main method of anesthesia was local infiltrative anesthesia (69.6%). The overall incidence of postoperative complications was 15.6%. Strict observance of operating techniques, high-quality hemostasis, fullfledged conservative therapy allows avoiding the development of serious complications at various stages of treatment